Association between the aspartate aminotransferase-to-alanine aminotransferase ratio and the reversion to normoglycemia in people with impaired fasting glucose: a 5-year retrospective cohort study - Zhang, Kebao; Chen, Lidan; Deng, Zhe; Rong, Rong; Xu, Lifen; Xu, Liting; Zeng, Shuting; Hu, Haofei (Frontiers in Endocrinology, 2025)
BackgroundStudies have shown that the aspartate aminotransferase (AST)/alanine transaminase (ALT) ratio is related to prediabetes, diabetes, and diabetes complications. However, there is limited evidence proving that the AST/ALT ratio is correlated with blood glucose reversal in patients with impaired fasting glucose (IFG). In this study, we analyzed the relationship between the AST/ALT ratio and blood glucose reversal in a large group of Chinese individuals with impaired fasting blood glucose.MethodsParticipants were recruited from the Rich Healthcare Group’s physical examinations from 2010 to 2016. Among them, 11,121 Chinese adults were selected for enrollment in this study. Cox proportional hazards regression was used to identify the association between the AST/ALT ratio and blood glucose reversal to normoglycemia in individuals with IFG. A generalized additive model (GAM) and smooth curve fitting were used to identify a nonlinear relationship between the AST/ALT ratio and blood glucose reversal. In addition, sensitivity analyses and subgroup analyses were used to test the reliability of our study.ResultsThe AST/ALT ratio was found to be independently related to blood glucose reversal in pre-diabetic populations of Chinese adults (HR = 1.20, 95%CI = 1.11–1.30, p < 0.00001). A nonlinear relationship was found between the AST/ALT ratio and reversion to normoglycemia. On the right side of the inflection point, the AST/ALT ratio was actively related to blood glucose reversal in populations with IFG (HR = 1.37, 95%CI = 1.23–1.52, p < 0.0001). However, on the left side of the inflection point, the relationship was not closely related. Sensitivity analyses, competing risk multivariate Cox regression, and subgroup analyses also confirmed the study results.ConclusionOur study revealed that the AST/ALT ratio is independently related to reversion to normoglycemia in pre-diabetic Chinese people. The relationship between the AST/ALT ratio and reversion to normoglycemia from IFG is nonlinear. There is a significant positive relationship between the AST/ALT ratio and reversion to normoglycemia when the AST/ALT ratio is >1.13.